OPPORTUNITIES TO ATTRACT CAPITAL THROUGH THE STOCK MARKET IN UZBEKISTAN - A.T.Alikulov (Scholar Express Journals, 2023)
The article examines the share of segments of the financial market in attracting financial resources of corporate structures in Uzbekistan. The capital valuation of stock market instruments and loans of commercial banks in Uzbekistan was analyzed by comparison. It is indicated that in Uzbekistan there are opportunities to attract resources through the instruments of the stock market. In addition, scientific proposals and practical recommendations have been developed aimed at eliminating existing shortcomings in attracting financial resources through the stock market
Keywords: Financial market; capital market; Advisory Service